Collaborative Leadership as a Catalyst in Optimizing the Quality of Education at Elementary School - Ridlo, Wildani; Sofiana, Arina Nur; Sabarudin, Sabarudin (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This study explores the implementation of collaborative leadership as a catalyst component in optimizing educational quality at Ngrandulor State Elementary School in Jombang. The research focuses on investigating the mechanisms of collaborative leadership in constructing synergy between stakeholders and the community and analyzing its implications for improving educational standards. The research methodology applied is a qualitative approach with systematic observation, in-depth interviews, and comprehensive documentary analysis. The data analysis process was carried out through the condensation model developed by Miles, Huberman, and Saldana. Research findings indicate that implementing collaborative leadership contributes significantly to increasing the credibility of educational institutions from the community's perspective. This is manifested through a quantitative increase in students by 10% per year since 2021. This study's theoretical and practical implications affirm that collaborative leadership can be conceptualized as an efficient strategy for improving the quality of education. Its prerequisites are systemic support and active participation from all stakeholder elements. The research results provide a contemporary perspective on the complexity of implementing collaborative leadership models in the context of primary education institutions.